Effect of amlodipine, lisinopril and allopurinol on acetaminophen-induced hepatotoxicity in rats - Nesreen E.M. Mohammed; Basim A.S. Messiha; Ali A. Abo-Saif (Elsevier, 2016)
Background: Exposure to chemotherapeutic agents such as acetaminophen may lead to serious liver injury. Calcium deregulation, angiotensin II production and xanthine oxidase activity are suggested to play mechanistic roles in such injury. Objective: This study evaluates the possible protective effects of the calcium channel blocker amlodipine, the angiotensin converting enzyme inhibitor lisinopril, and the xanthine oxidase inhibitor allopurinol against experimental acetaminophen-induced hepatotoxicity, aiming to understand its underlying hepatotoxic mechanisms. Material and methods: Animals were allocated into a normal control group, a acetaminophen hepatotoxicity control group (receiving a single oral dose of acetaminophen; 750 mg/kg/day), and four treatment groups receive N-acetylcysteine (300 mg/kg/day; a reference standard), amlodipine (10 mg/kg/day), lisinopril (20 mg/kg/day) and allopurinol (50 mg/kg/day) orally for 14 consecutive days prior to acetaminophen administration. Evaluation of hepatotoxicity was performed by the assessment of hepatocyte integrity markers (serum transaminases), oxidative stress markers (hepatic malondialdehyde, glutathione and catalase), and inflammatory markers (hepatic myeloperoxidase and nitrate/nitrite), in addition to a histopathological study. Results: Rats pre-treated with amlodipine, lisinopril or allopurinol showed significantly lower serum transaminases, significantly lower hepatic malondialdehyde, myeloperoxidase and nitrate/nitrite, as well as significantly higher hepatic glutathione and catalase levels, compared with acetaminophen control rats. Serum transaminases were normalized in the lisinopril treatment group, while hepatic myeloperoxidase was normalized in the all treatment groups. Histopathological evaluation strongly supported the results of biochemical estimations. Conclusion: Amlodipine, lisinopril or allopurinol can protect against acetaminophen-induced hepatotoxicity, showing mechanistic roles of calcium channels, angiotensin converting enzyme and xanthine oxidase enzyme in the pathogenesis of hepatotoxicity induced by acetaminophen.